From pots to profits: financial literacy among street food entrepreneurs in Sarawak - Morshidi, Ummi Nadirah; Latip, Malisah (Universiti Teknologi MARA, 2024)
The COVID-19 pandemic has not only caused health problems but also posed significant economic challenges to countries around the world. These challenges are also experienced by street vendors who strive to maintain their business activities. Street vendors thus operate in an uncertain and unpredictable environment, coupled with changing customer tastes, government restrictions and limited access to financial resources. In response to these challenges, this study examined the level of financial literacy of 106 street food vendors (SFVs) in Bintulu, Sarawak, and its influences on business performance and access to credit. The findings found a correlation between financial knowledge and business performance, highlighting the importance of financial knowledge in achieving the success of business operations. Similarly, prudent financial behaviour is seen as a critical factor in managing economic uncertainty and strengthening business resilience. However, the relationship between financial attitude and business performance does not seem significant and requires further investigation. Through multiple regression analysis, this study explains the medium predictive power of financial literacy determinants on access to credit. By shedding light on the financial literacy level associated with street vendors, this research supports targeted interventions to improve SFVs’ financial resilience and sustainability. The significance of the results of this study goes beyond academic investigation. Policymakers and relevant stakeholders can use these findings to develop specific strategies to support SFVs in the face of economic challenges, facilitate access to credit, and promote financial literacy initiatives. In addition, the findings from this study can be used as a basis for designing and implementing programs primarily related to financial literacy that address the unique needs of micro-entrepreneurs, thus promoting socio-economic development and resilience in the face of adversity.